Comparison of Ecoprint Results on Cotton and Silk Materials Using Cassava Leaves with Hammering Technique Using Lime Mordant - Frederica, Irene; Adriani, Adriani (LPPM Institut Seni Indonesia Padangpanjang, 2024)
This research is motivated by an effort to reduce the negative impact caused by the use of synthetic dyes on the environment by using cassava leaves as an environmentally friendly ecoprint textile motif. The aim of this research is to describe the direction of color (hue), clarity of motif shape, washing resistance and explain differences in color direction (hue), clarity of motif shape and washing resistance of ecoprint results on cotton and silk materials using whiting mordant. The type of research is experimental research. The data in this research uses primary data with data collection techniques in the form of questionnaires. The data analysis technique uses frequency percentage and data analysis uses the SPSS (Statistical Product and Service Solution) program. What was produced in this research was the name of the color on the ecoprint of cotton material using whiting mordant, resulting in Sepia Brown color on cassava leaves and Muddy Waters Brown color on cassava leaf bones with clarity of motif shape in the very clear category and washing resistance in the good category. Silk material using whiting mordant produces Soft Brown color on cassava leaves and Clam Shell Pink color on cassava leaf bones with a very clear category and washing resistance in the good category.